Feedback of patients' evaluations of general practice care: a randomised trial. Issue 4 (1st December 2001) - Vingerhoets, E; Wensing, M; Grol, R
Abstract : Objective —To assess the effects of feedback of patients' evaluations of care to general practitioners. Design —Randomised trial. Setting —General practice in the Netherlands. Subjects —55 GPs and samples of 3691 and 3595 adult patients before and after the intervention, respectively. Interventions —GPs in the intervention group were given an individualised structured feedback report concerning evaluations of care provided by their own patients. Reference figures referring to other GPs were added as well as suggestions for interpretation of this feedback, an evidence-based overview of factors determining patients' evaluations of care, and methods to discuss and plan improvements. Main outcome measures —Patients' evaluations of nine dimensions of general practice measured with the CEP, a previously validated questionnaire consisting of 64 questions, using a six point answering scale (1=poor, 6=very good). Results —Mean scores per CEP dimension varied from 3.88 to 4.77. Multilevel regression analysis showed that, after correction for baseline scores, patients' evaluations of continuity and medical care were less positive after the intervention in the intervention group (4.60 v 4.77, p<0.05 and 4.68 v 4.71, p<0.05, respectively). No differences were found in the remaining seven CEP dimensions. Conclusions —Providing feedback on patients' evaluations of care to GPs did not result in changes in their evaluation of the care received. This conclusion challenges the relevance of feedback on patients' evaluations of care for quality improvement.